WORK LIFE BALANCE: ITS IMPACT TO THE WELL BEING OF OVERSEAS FILIPINO WORKERS - Misajon, Mervyn J.; Catalan-Opulencia, Maria Jade (International Journal of Psychosocial Rehabilitation, 2020)
There has been dramatic change that occurred in the labor market and demographic profile over the past few decades. To address the issue, new orientations towards life-long learning, personal and career development, and an increased awareness and need for a balance between work and life was given priority by most organizations. The study examined on Overseas Filipino Workers(OFW) representing various sectors to determine the work life balance and how it affects their well being. Descriptive method was used utilizing sequential explanatory design, convenient sampling in data gathering and employed content analysis. The findings indicated that on the part of OFW, he/she has adjusted himself to make strategies to maintain the balance between the two realms in life- work and family. Work-life balance is a broad and complex phenomenon and it affects many people working in their host countries